The Impact of the Fusarium Toxin Deoxynivalenol (DON) on Poultry - Awad, W.A.; Ghareeb, K.; Bohm, J.; Razzazi, E.; Hellweg, P.; Zentek, J. (International Journal of Poultry Science, 2008)
Deoxynivalenol (DON), a trichothecene, is prevalent worldwide in crops used for food and feed production. The presence of mycotoxins in poultry feeds is a significant factor for financial losses to animal industries. Although DON is one of the least acutely toxic trichothecenes, it should be treated as an important food safety issue because it is a common contaminant of grains. Special care must be taken in so-called “Fusarium years”. As poultry is regarded to be less sensitive to DON compared to other species it is suspected to divert the infected cereal batches to poultry feeding. This review focuses on the ability of DON to induce toxicologic and immunotoxic effects in chickens. Chickens and laying hens respond to increasing dietary DON concentrations with a reduction in productivity only at high levels above 5mg/kg but there is no clear evidence of a dose-response relationship. The main effect at low dietary concentrations appears to be a reduction in food consumption (anorexia), while higher doses induce severe reduction in weight and impaired resistance to infection, particularly bacterial infection. One important aspect of DON toxicity is injury to the gastrointestinal tract. DON has an influence intestinal morphology of chickens, especially in the duodenum and jejunum, as evidenced by shorter and thinner villi. Additionally, DON decreased the intestinal nutrients absorption (glucose and amino acid) in the chicken small intestine in vivo and In vitro. The capacity of DON to alter normal immune function has been of particular interest. There is extensive evidence that DON impairs the immune function in broiler and Leghorn chicks. DON induced changes in the haematopoietic system of chicks and altered the mitogen-induced proliferation of lymphocytes. The feeding of DON contaminated grains decreases serum antibody titers against Newcastle disease virus (NDV) and infectious bronchitis virus (IBV) in laying hens and broilers. Other effects include superinduction of cytokine production by T helper cells (In vitro) and activation of T cells to produce a proinflammatory cytokine. To what extent the elevation of cytokines contributes to metabolic effects such as decreased feed intake remains to be established. Further toxicological studies on the impact of DON in the immune system and gastrointestinal tract of poultry are warranted.